Reduction of Nitrite Levels in Edible Bird Nest on Lombok Island with Alkali Solution and Oxygen Water - Alvin Juniawan; Arista Suci Andini; Syuhriatin (Postgraduate, University of Mataram, 2025)
In this study, sampling was carried out at 3 locations of swallow nest farmers, namely in East Lombok, Central Lombok and West Lombok. The type of swallow nest used in this study was the Linchi swallow nest. This study was a quantitative study, namely to find the best variation in soaking time with alkaline water and Oxygen Water to reduce nitrite levels. Sample measurement using a Uv-Vis spectrophotometer instrument and characterization using FTIR. The results of the study showed the highest reduction in nitrite levels using an alkaline solvent with a pH of 7.5, Central Lombok, East Lombok and West Lombok Edible Bird’s Nest Sample, respectively, as follows: 87.88%; 96.26%; and 94.59% with an optimum contact time of 30 minutes. While the highest reduction in nitrite levels for Central Lombok, East Lombok and West Lombok, Edible Bird’s Nest samples were as follows: 92.51%; 98.5%; and 97.85% with an optimum contact time of 15 minutes. This is also supported by FTIR spectra data from optimum conditions for reducing nitrite levels where the characteristics of the FTIR spectra in the 1400 cm-1 wavenumber region have a %T value after treatment> to %T before treatment. The results of the macronutrient test showed that the bird's nest contains carbohydrates, proteins and lipids. While the results of the phytochemical test showed that the bird's nest sample contained phenolic compounds. In this study, it has been successfully reduced nitrite levels in bird's nests using alkaline solvents pH 7.5 and Oxygen Water which is the latest method that is cheaper and more efficient.